Identifikasi Problematika Pendidikan Di Sekolah Dasar MIS Modern Az-Zakky - Dewi Sinta Elisabet Hutahaean; Elma Christin Sinaga; Grace Keren Hapukh Mendrofa; Monika Juliana Bai Sipangkar; Rahimah Khairani (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2024)
Basic education is the primary foundation in the development of human and societal quality. However, the quality of learning in primary schools is often influenced by the availability of adequate educational facilities. This study aims to identify educational problems at MIS Modern Az-Zakky Elementary School through a literature review and fishbone analysis. In this study, we collected and analyzed various relevant literature on the topic. The analysis results show that several educational problems, such as inadequate classrooms, insufficient learning equipment, and other supporting facilities, can significantly affect the quality of learning in primary schools. Existing educational problems can hinder the learning process, reduce student interest in learning, and lower students' academic achievement. Additionally, the impact of these problems can worsen educational disparities and the overall quality of education.